Electrolytes Levels (Na, K, Cl) in Serum Stored at 4°C Temperature - Fauziah, Amalia Nurul; Martsiningsih, M. Atik; Setiawan, Budi (Universitas Nahdlatul Ulama Surabaya, 2021)
The samples used for serum electrolyte measurement should be analyzed immediately after being received in the laboratory within 1-2 hours to avoid an increase in the error of the results. Serum should be stored at 4°C for a period to prevent damage. The analyst should consider maximum delay time in the examination to maintain the serum's quality. This study compared the 2-hour and 3-hour delays in sodium (Na), potassium (K), and chlorine (Cl) tests. The method used in this study is an observational analysis with a cross-sectional study design. The samples in this study used 35 patient serum residues. The study was conducted in November 2020 with a continuous sampling technique. Electrolyte levels in the sample were measured by AVL 9180 Electrolyte Analyzer using Ion-Selective Electrode (ISE) method. The differences in electrolyte (Na, K, Cl) levels were analyzed by the Kruskal-Wallis Statistical test at a 95% confidence level. The results showed that the content of sodium, potassium, and chlorine were 0.719; 0.976; and 0.772. This study showed that there was no significant difference in the electrolyte content of sodium (Na), potassium (K), and chlorine (Cl) in the serum directly detected from the serum stored at 4°C for 2 hours and 3 hours. In conclusion, it is acceptable to postpone the serum test for 3 hours with various considerations.